IDENTIFIKASI DISTRIBUSI POLA CURAH HUJAN DAN NERACA AIR KOTA DENPASAR - Daryono - (Bumi Lestari Journal of Environment)
Identification on rainfall pattern and water balance is very important for environtmentresearch, water resources development and agricultural planning. This study used statistical andThornthwaite and Mather (1957) method to analyse the water balance. The results show that wetseason at Denpasar take place on November up to April and dry season take place on May up toOctober in every years. Water surplus period at Denpasar take place for 4 months (January-April) in amount 496 mm. Water deficit period take place for 6 months (May-October) in amount298 mm.